Grazing management affects fish diets in a Wadden Sea salt marsh. (15th November 2018) - Friese, Julia; Temming, Axel; Dänhardt, Andreas
Abstract: Salt marshes provide favourable feeding conditions for fish thanks to a variety of food sources including terrestrial prey, which can be negatively affected by livestock grazing. We evaluated the seasonal effect of sheep grazing on fish diets in a Wadden Sea salt marsh. Consumed quantities and frequencies of terrestrial prey differed between predators. While terrestrial prey was unimportant for herring and sand goby, common goby and three-spined sticklebacks consumed it immediately during winter, when it became available through marsh flooding. In contrast to the relative stomach content weights, the stomachs content compositions differed between grazing treatments. Sticklebacks consumed terrestrial prey more often and in higher amounts in the ungrazed than in the grazed marsh. Using random forest models, the importance of grazing management for fish compared to other influencing factors was analysed based on sticklebacks. Its most important terrestrial prey was the energy-rich and probably easy to catch amphipod Orchestia gammarellus . Both the ratio of fishes feeding on Orchestia and the consumed amount of Orchestia depend mainly on the accessibility, determined by the flooding height and duration. The abundance of Orchestia was the second most important factor determining its consumed amounts. Orchestia densities are significantly reduced by sheep grazing. Therefore, sheep grazing has a negative impact on fish feeding opportunities in winter, when marine prey on the tidal flats is scarce. To improve the feeding habitat value of Wadden Sea salt marshes for fish it is advisable to keep lower elevated marshes with large creeks ungrazed. Graphical abstract: Image 1 Highlights: Sheep grazing reduces the abundance of the main terrestrial prey for fish. Sheep grazing reduces the consumption of the terrestrial prey by fish. Not all fish species use terrestrial prey in salt marshes. Flooding is more decisive for terrestrial prey consumption than grazing management. Fish find enough prey in the grazed marsh to compensate missing terrestrial prey.